“Black Mary”? Mary Countess Coudenhove-Taaffe’s charity work during the First World War (Theatrum historiae, 2024)
The subject of this case study is an analysis of the charitable activities of Mary Countess Coudenhove, née Taaffe, during World War I. From her position as the wife of the Governor of Bohemia, she entered the public sphere as a protector of charitable events, a supporter of institutions caring for wounded soldiers and orphaned children (especially war orphans), an initiator of her own charitable projects, and an intercessor for third parties, in addition to working as a nurse in one of Prague’s Red Cross reserve hospitals. The scope and reach of her charitable activities, which were partly official, were exceptional in many respects. During World War I, she was undoubtedly one of the best-known personalities of Prague’s charitable society. In her public activities she acted as a supporter of the Habsburg dynasty and in the eyes of society she was regarded, like her husband, as one of the symbols of the monarchy and its elites. The Countess was forced to face hostile attacks, and shortly after the declaration of an independent Czechoslovakia she was interned with her husband and sister and accused of stealing Red Cross property. These accusations were never proved.
Keywords: Charity; World War I; Aristocracy; Noblewomen; Coudenhove; Taaffe